Kognitif Pengelola Badan Layanan Umum dalam Mengelola Kekayaan di Perguruan Tinggi Keagamaan Islam Negeri - Slamet; Achmad Diny Hidayatullah; Imam Bani Mustolik (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aims to analyze the knowledge (cognitive) of the Public Service Agency manager in managing university assets. This research was conducted at three State Islamic Religious Universities that have received the mandate of the Public Service Agency, including the State Islamic University of Sunan Ampel Surabaya, Sunan Kalijaga Yogyakarta, and Walisongo Semarang. Data collection was carried out using in-depth interviews with an unstructured approach. The key informants in the research were the chancellor, vice-rector and head of the general affairs bureau, and the head of the business unit. Data analysis used domain analysis and content analysis methods. The study results indicate that the knowledge of the Public Service Agency manager at the Islamic Religious College is still at the stage of applying the regulations on the Public Service Agency. There have not been many thoughts on the management of the Public Service Agency that analyze and evaluate the mandate of the Public Service Agency from the government. Moreover, creating or developing asset management owned. In general, the cognitive management of the Public Service Agency at Islamic Religious Universities is not total. This condition has an impact that is not optimal in managing assets as a source of non-academic higher education income.